2019
DOI: 10.3168/jds.2018-16168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of feeding diets diluted with sorghum-sudangrass silage or low-quality grass on nutrient intake and digestibility and growth performance of Holstein dairy heifers

Abstract: This study was carried out to evaluate the nutrient intakes and growth of dairy heifers offered an alfalfa silage-corn silage diet (CON; 14.3% crude protein, 61.1% total digestible nutrients, 47.9% neutral detergent fiber) compared with diets containing 1 of 2 types of sorghumsudangrass (SS) silages: conventional or photoperiod sensitive. The objective of the study was to determine the potential to use SS to control dry matter (DM) and nutrient intakes and weight gain. Both diets were similar in nutrient compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…When calculated on a % of BW basis, NDF intake was close to 1% of BW (0.95-0.99% of BW as NDF), which is consistent with the work by Hoffman et al (2008) that found heifers eat approximately 1.0% of BW in NDF daily when offered high forage diets at ad libitum intakes. Several other studies with feeding higher fiber, lower energy diets for ad libitum intakes have also shown reduced intakes of DM and energy similar to our results (Greter et al, 2008;Coblentz et al, 2012Coblentz et al, , 2015Su et al, 2017;Li et al, 2019b). Starch intake was greater (P < 0.01) for heifers fed the HE diet (1.7 kg/d) compared with the LE diet (1.1 kg/d), primarily because there was a greater amount of corn silage in the HE diet.…”
Section: Nutrient Intakessupporting
confidence: 89%
See 3 more Smart Citations
“…When calculated on a % of BW basis, NDF intake was close to 1% of BW (0.95-0.99% of BW as NDF), which is consistent with the work by Hoffman et al (2008) that found heifers eat approximately 1.0% of BW in NDF daily when offered high forage diets at ad libitum intakes. Several other studies with feeding higher fiber, lower energy diets for ad libitum intakes have also shown reduced intakes of DM and energy similar to our results (Greter et al, 2008;Coblentz et al, 2012Coblentz et al, , 2015Su et al, 2017;Li et al, 2019b). Starch intake was greater (P < 0.01) for heifers fed the HE diet (1.7 kg/d) compared with the LE diet (1.1 kg/d), primarily because there was a greater amount of corn silage in the HE diet.…”
Section: Nutrient Intakessupporting
confidence: 89%
“…The current study had lower DMI and energy intakes for both diet treatment groups ( 10 2001) predictions for a 520 kg of BW heifer (average of initial and final study weights) at 150 d pregnant were 12.7 kg of DMI, and 25.9 Mcal of ME for 0.9 kg of gain/d and 29.6 Mcal of ME for 1.17 kg of gain/d. As discussed previously, we have observed this in the freestall facility for previous studies (Coblentz et al, 2015;Su et al, 2017;Li et al, 2019b) and may be due to reduced energy use for exercise and reduced maintenance requirements in freestall or other confinement situations in which heifers have feed access and laying space in a small pen and have minimal environmental stress (Fox and Tylutki, 1998).…”
Section: Nutrient Intakessupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, due to its strong stress resistance, high temperature resistance, drought resistance, salt and alkali resistance, P. giganteum is easy to plant with high yield, which can effectively improve the shortage of forage resources and further reduce the feed grain ( Hayat et al, 2020 ; Li et al, 2020 ). It has been shown that P. giganteum can replace corn silage, Sorghum sudanense and other conventional forages as livestock feed ( Li et al, 2019 ). Therefore, P. giganteum is the best choice for high-quality feed for animal husbandry.…”
Section: Introductionmentioning
confidence: 99%